Evaluation of the physical condition of gymnasts who specialize in team routines - Udalova M.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to creation of assessment exercises to gauge the physical condition of gymnasts participating in team routines. Methods and structure of the study. Athletes participating in the Masters of Sports program engaged in scientific research. The evaluation tasks, based on the definition of gymnasts' physical fitness, included standards for assessing the level of flexibility, strength, coordination, speed, and special endurance. The evaluation scale for gymnasts' physical fitness was created using average standards for the advanced level in rhythmic gymnastics. Results and conclusions. The framework of the tasks encompasses both the fundamental principles of pedagogy, applied to the structured educational process, and the principles of sports training, which establish the necessary connections between the training impact and its consequences. The developed assessment instruments will enable professionals to make timely modifications to the training regimen and develop their own approach to sports training. The developed test tasks will enable coaches to effectively tailor the training regimen and enhance the physical fitness of gymnasts participating in group exercises.